2019
DOI: 10.3390/s19235297
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a New Inertial Sensor Based System with an Optoelectronic Motion Capture System for Motion Analysis of Healthy Human Wrist Joints

Abstract: This study aims to compare a new inertial measurement unit based system with the highly accurate but complex laboratory gold standard, an optoelectronic motion capture system. Inertial measurement units are sensors based on accelerometers, gyroscopes, and/or magnetometers. Ten healthy subjects were recorded while performing flexion-extension and radial-ulnar deviation movements of their right wrist using inertial sensors and skin markers. Maximum range of motion during these trials and mean absolute difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 29 publications
0
37
2
Order By: Relevance
“…A study of MR spine lumbosacral (2015.08. 14) showed reduced intervertebral discs L4/L5, L5/S1, with reduction of their hydration, and bilateral narrowed intervertebral foramina L4/L5, L5/S1. At L4/L5 level, the central-right-side protrusion of the intervertebral disc is about 6.5 mm intrathecally with the impression of the right nerve root.…”
Section: Cases Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of MR spine lumbosacral (2015.08. 14) showed reduced intervertebral discs L4/L5, L5/S1, with reduction of their hydration, and bilateral narrowed intervertebral foramina L4/L5, L5/S1. At L4/L5 level, the central-right-side protrusion of the intervertebral disc is about 6.5 mm intrathecally with the impression of the right nerve root.…”
Section: Cases Descriptionmentioning
confidence: 99%
“…ProMove Mini system was tested and compared with the Motion Capture System: Tech-MCS Inertial Measurement Unit (a fully wireless motion analysis solution). Some of methods comparison IMU vs OMC were presented in [14].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used methods to compare the accuracy of the IMU data use of special sensors such as the camera-based 3D motion analyzers. IMU devices have widely been used for spatio-temporal gait analysis and their performance compared against motion capture systems [25], [26]. Results have shown that the reliability and accuracy of a low-cost IMUbased system outperformed those obtained from different motion capture systems [27], [28].…”
Section: A Related Workmentioning
confidence: 99%
“…The accuracy of IMU is dependent on the exact sensor and software specification used. In a previous study, we investigated an IMU system for measurement of basic motion tasks of the wrist and found it to be feasible for clinical application with similar measurements to the gold standard, an OMC based system [ 9 ]. However, as task-specific validation of a new system is necessary for possible clinical application, the high accuracy in basic motion tasks cannot be automatically assumed for more complex movements of daily living such as the DTM [ 1 ].…”
Section: Introductionmentioning
confidence: 99%